Application of the Leslie Matrix on Female Birth Rates and Life Expectancy in the Special Region of Yogyakarta - Lianingsih, Nestia; Haq, Fadiah Hasna Nadiatul; Audina, Yurid (Research Collaboration Community (RCC), 2024)
This study aims to predict the number and growth rate of the female population in the Special Region of Yogyakarta for 2025, using the Leslie Matrix model. The matrix utilizes fertility rates and female life expectancy across different age intervals. The data used includes the female population from 2015 and 2020, alongside Age-Specific Fertility Rate (ASFR) data for the same period. By applying the dominant eigenvalue of the Leslie matrix, the study finds that the growth rate of the female population in Yogyakarta is projected to increase, with a dominant eigenvalue of 1.252. The female population is predicted to reach 2,409,852 by 2025, an increase from 1,983,800 in 2020. These findings are expected to inform population management and development planning in Yogyakarta.